Contribution to the study of blastomycosis - Lozada Benavente, Samuel (1920)
The study of blastomycosis has gained importance, for the reason that in recent times has been pointed out the great discussion of the condition, therefore its geographic location located in the heart of tropical America, offered in Bolivia, Brazil and Peru the largest number of clinical specimens, and the more important knowledge for us, because of his characterization that has given ground to separate the group of tropical ulcers, known by the common name Espundia, a set of clinical cases where it is not leishmania was the producer, and in which Dr. E. Escomel found in 1914, for the first time in Peru, a fungus of the genus Blastomiceto.